Methane thermometry in deep-sea hydrothermal systems: Evidence for re-ordering of doubly-substituted isotopologues during fluid cooling. (1st November 2020) - Labidi, J.; Young, E.D.; Giunta, T.; Kohl, I.E.; Seewald, J.; Tang, H.; Lilley, M.D.; Früh-Green, G.L.
Abstract: Deep-sea hydrothermal fluids are often enriched in carbon dioxide, methane, and hydrogen. Methane effuses from metal-rich black smokers such as the Rainbow hydrothermal field, at temperatures higher than 200 °C. At the Lost City field, CH4 emanates from alkaline fluids at <100 °C. The abundance of the rare, mass-18 CH4 isotopologues, 13 CH3 D and 12 CH2 D2, can mitigate degeneracies in the conventional isotopic signatures of methane. We studied the isotopologue compositions of methane from the Rainbow, Lucky Strike, Von Damm, and Lost City hydrothermal fields. At Rainbow, where the vented fluids are at ∼360 °C, our coupled Δ 12 CH2 D2 - Δ 13 CH3 D data establish that methane is in internal equilibrium at 343 - 35 + 41 °C. This may track the formation temperature of abiotic methane, or it may be the result of equilibration of methane isotopologues within the carrier fluid. Lucky Strike and Von Damm have fluid temperatures <300 °C and although Δ 13 CH3 D values are indistinguishable from those at Rainbow, 12 CH2 D2 abundances are marginally higher. At Lost City, Δ 13 CH3 D data show a range of values, which at face value correspond to apparent temperatures of between 265 - 24 + 28 °C and 158 - 14 + 16 °C, far hotter than fluid temperatures. A unique aspect of the Lost City data is the range of large 12 CH2 D2 excesses. The Δ 12 CH2 D2 data correspond to temperatures of between 101 - 8 + 9 °C and 69 - 4 + 4 °C, showing a near-perfect match with fluid temperatures. We find that mixing scenarios involving microbial methane may not account for all of the isotope data. We suggest that Δ 12 CH2 D2 values, unlike Δ 13 CH3 D values, are prone to near-complete re-equilibration at host fluid temperatures. We suggest that 13 CH3 D isotopologue data are consistent with abiotic methane being synthesized at ∼350 °C. On the other hand, 12 CH2 D2 isotopologue ordering records post formation residence temperatures. We explore a possible mechanism decoupling the re-equilibration systematics of the doubly-substituted isotopologues.